Indonesia - Chalmers, Ian (OUP, 2006)
The book explores the social and cultural dynamics of political change in Indonesia since the mid-1990s. Within an historical framework, the book examines a number of traditions which prevail in Indonesian society and analyzes their contemporary relevance